Assessment of 99mTc-NTP 15-5 uptake on cartilage, a new proteoglycan tracer: Study protocol for a phase I trial (CARSPECT) - Thivat, Emilie; Chanchou, Marion; Mathieu, Sylvain; Levesque, Sophie; Billoux, Tommy; Auzeloux, Philippe; Sas, Nicolas; Molnar, Ioana; Jouberton, Elodie; Rouanet, Jacques; Fois, Giovanna; Maigne, Lydia; et al. (Frontiers in Medicine, 2022)
Background: 99mTc-NTP 15-5 is a SPECT radiotracer targeting proteoglycans (PG), components of the cartilaginous extracellular matrix. Imaging of PGs would be useful for the early detection of cartilage disorders (osteoarthritis, arthritis and chondrosarcoma, Aromatase Inhibitor associated arthralgia (AIA) in breast cancer), and the follow-up of patients under treatment. According to preclinical study results, 99mTc-NTP 15-5, is a good candidate for a specific functional molecular imaging of joints. We intend to initiate a first in-human study to confirm and quantify 99mTc-NTP 15-5 uptake in healthy joints. Methods: As the clinical development of this radiotracer would be oriented towards the functional imaging of joint pathologies, we have chosen to include patients with healthy joints (unilateral osteoarthritis of the knee or breast cancer with indication of AI treatment). This phase I study will be an open-label, multicenter, dose-escalation trial of a radiopharmaceutical aiming to determine the recommended level of activity of 99mTc-NTP 15-5 to obtain the best joint tracer contrasts on images, without dose limiting toxicity (DLT). The secondary objectives will include the study of the pharmacology, biodistribution (using planar whole body and SPECT-CT acquisitions), toxicity and dosimetry of this radiotracer. The dose escalation with 3 activity levels (5, 10 and 15 MBq/kg), will be conditioned by the absence at the previous level of DLT and of a visualized tracer accumulation on more than 80% of healthy joints as observed on scintigraphy performed at ≤ 2 h post-injection. Discussion: This first in-human phase I trial will be proof-of-concept of the relevance of 99mTc-NTP 15-5 as a cartilage tracer, with the determination of the optimal methodology (dose and acquisition time) to obtain the best contrast to provide a functional image of joints with SPECT-CT. Trial registration number: Clinicaltrials.gov:NCT04481230. Identifier in French National Agency for the Safety of Medicines and Health Products (ANSM): N°EudraCT 2020-000495-37.